The Conspiracy of Equals: Rolls & Friends - Marrone, Gianfranco (E|C, 2020)
The essay reconstructs the events of “involtini”, a very popular dish in Italian cuisine, in order to trace the specificities of the Sicilian recipes. In particular, a corpus of recipes is analyzed in order to identify the recurring narrative programs in the preparation of the Sicilian “involtini”, distinguishing variations and invariant forms. Particular attention is given to the conformation of the gastronomic object itself and its arrangement on the plate. By comparing other types and sizes of similar gastronomic objects, it is highlighted how cultural and political meanings can be identified in the sense of the “involtini”.